Liquid-liquid separation of azeotropic mixtures of ethanol/alkanes using deep eutectic solvents: COSMO-RS prediction and experimental validation - Hadj-Kali, M.K.; Hizaddin, H.F.; Wazeer, I.; El blidi, L.; Mulyono, S.; Hashim, M.A. (Elsevier, 2017)
Separation of azeotropic mixtures is a topic of great industrial interest. In this work, liquid-liquid extraction using deep eutectic solvents (DESs) is explored to separate binary azeotropic mixtures of ethanol and n-hexane, n-heptane or n-octane. Ten DESs were screened using the COSMO-RS approach by predicting the activity coefficient at infinite dilution, γ∞ of ethanol and n-alkanes in each DES. Then, three DESs were selected for experimental validation where Tetrabutylammonium bromide/Levulinic acid (TBAB/LA) with a molar ratio (1:2) gave the best extractive performance for all systems. Ternary liquid-liquid extraction experiments were conducted at room temperature with this DES. It was found that the tie-lines of all systems have positive slopes, indicating that a small amount of solvent is required to extract ethanol. Moreover, the distribution ratio and selectivity values are all greater than unity and the DES was not detected in the raffinate phase which indicate minimal cross-contamination between extract and raffinate phases. Finally, COSMO-RS predictions of the ternary tie-lines were in excellent agreement with experimental data, with an average RMSD value of 1.65%. The experimental data were also successfully correlated with NRTL model with an average RMSD value of 1.50%.